The Roles Of Ferric Uptake Regulator (Fur) For Plant Root Attachment By Burkholderia sp. USMB20 - Shaffie, Salwani (2018)
Attachment is an early step during bacterial plant root colonization process. Bacteria need iron as an essential component for its growth and cellular processes. Ferric uptake regulator (Fur) is a global regulator that controls bacterial iron uptake. This study investigated the roles of Burkholderia sp. USMB20’s Fur in controlling iron uptake during plant root attachment. USMB20 Fur minus mutant (USMB20Efur) was used as comparison. The observation showed USMB20 recorded highest number of attached cell on root surface in 50μM of ferric concentration, where as USMB20Efur recorded less numbers of attached cell. Scanning Electron Microscope (SEM) showed dense attachment of cells on the root surface compared to the USMB20Efur.